2001
DOI: 10.1051/0004-6361:20010081
|View full text |Cite
|
Sign up to set email alerts
|

Dust-penetrated morphology in the high-redshift universe: Clues from NGC 922

Abstract: Abstract.Results from the Hubble Deep Field (HDF) North and South show a large percentage of high-redshift galaxies whose appearance falls outside traditional classification systems. The nature of these objects is poorly understood, but sub-mm observations indicate that at least some of these systems are heavily obscured (Sanders 2000). This raises the intriguing possibility that a physically meaningful classification system for high-redshift galaxies might be more easily devised at rest-frame infrared wavelen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…This variation might indicate some dynamical interaction between the two bars, such as an oscillation about the equilibrium aligned configuration. Block et al (2001) have suggested that a physically meaningful classification system for high-redshift galaxies may be more easily devised at rest-frame infrared wavelengths, rather than in the optical regime. Sub-mm observations indicate that at least some of these systems are heavily obscured by dust (Sanders 1999).…”
Section: Bar Torque and Form Familymentioning
confidence: 99%
See 3 more Smart Citations
“…This variation might indicate some dynamical interaction between the two bars, such as an oscillation about the equilibrium aligned configuration. Block et al (2001) have suggested that a physically meaningful classification system for high-redshift galaxies may be more easily devised at rest-frame infrared wavelengths, rather than in the optical regime. Sub-mm observations indicate that at least some of these systems are heavily obscured by dust (Sanders 1999).…”
Section: Bar Torque and Form Familymentioning
confidence: 99%
“…Lessons from our local Universe are that optical morphologies can be radically different from near-infrared ones; some optically flocculent galaxies, for example, may have beautiful grand design stellar disks when examined at K. The decoupling of gaseous and stellar disks can be dramatic (see e.g., Puerari et al 2000;Elmegreen et al 1999;Grosbøl & Patsis 1998;Block et al 1994). Block et al (2001) show that Fourier spectra may be generated on simulated Next Generation Space Telescope (NGST) rest-frame K post-stamp FITS images which may be as small as 1 on a side.…”
Section: Bar Torque and Form Familymentioning
confidence: 99%
See 2 more Smart Citations
“…In this contribution, the images of NGC 922 are simulated at redshifts z = 0.7 and z = 1.2 in the K ′ restframe. The original image of NGC 922 was obtained at the NASA Infrared Telescope Facility with NSFCam (more details can be found in Block et al 2001).…”
Section: Discussionmentioning
confidence: 99%